A New Design Paradigm for Smart Windows: Photocurable Polymers for Quasi‐Solid Photoelectrochromic Devices with Excellent Long‐Term Stability under Real Outdoor Operating Conditions. (28th December 2015) - Bella, Federico; Leftheriotis, George; Griffini, Gianmarco; Syrrokostas, George; Turri, Stefano; Grätzel, Michael; Gerbaldi, Claudio
Abstract : A new photoelectrochromic device (PECD) is presented in this work proposing the combination of a WO3 ‐based electrochromic device (ECD) and a polymer‐based dye‐sensitized solar cell (DSSC). In the newly designed architecture, a photocurable polymeric membrane is employed as quasi‐solid electrolyte for both the ECD and the DSSC. In addition, a photocurable fluoropolymeric system is incorporated as solution‐processable external protective thin coating film with easy‐cleaning and UV‐shielding functionalities. Such new polymer‐based device assembly is characterized by excellent device operation with improved photocoloration efficiency and switching ability compared with analogous PECDs based on standard liquid electrolyte systems. In addition, long‐term (>2100 h) stability tests under continuous exposure to real outdoor conditions reveal the remarkable performance stability of this new quasi‐solid PECD system, attributed to the protective action of the photocurable fluorinated coating that effectively prevents photochemical and physical degradation of the PECD components during operation. This first example of quasi‐solid PECD systems paves the way for a new generation of thermally, electrochemically, and photochemically stable polymer‐based PECDs, and provides for the first time a clear demonstration of their true potential as readily upscalable smart window components for energy‐saving buildings. Abstract : Light‐designed polymers are proposed as quasi‐solid electrolytes and ultraviolet‐cutting/easy‐cleaning coatings for photoelectrochromic devices (PECDs). Excellent coloration/bleaching performance as well as long‐term stability under real outdoor operating conditions is demonstrated. Thermally, electrochemically, and photochemically stable polymer‐based PECDs demonstrate for the first time their true potential as readily upscalable smart windows for modern energy‐saving buildings.